Regenerated polypropylene composite material with high surface smoothness and high paint adhesion and preparation method thereof
By using high-performance composite masterbatches in regenerated polypropylene materials, the modified chlorinated polypropylene and epoxy resin are driven to disperse on the surface layer, and the layered structure of talc powder is used to adsorb the paint components, the problems of poor adhesion and low surface finish of the regenerated polypropylene materials are solved, and the effects of high adhesion and high finish are achieved.
Patent Information
- Application Number
- CN202411978031.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Recycled polypropylene materials have problems such as poor paint adhesion and low surface finish in the application of spray painted parts, which limits its further development in automotive exterior bumpers and other fields.
High-performance composite masterbatches are used to replace traditional talc powder + additives, and ultra-high fluidity polypropylene drives the modified chlorinated polypropylene and epoxy resin to be evenly dispersed on the surface of the material, improving the surface polarity of the composite system, and using a layered structure with a high diameter and thickness ratio talc powder to adsorb the paint components.
It significantly improves the paint adhesion and surface finish of recycled polypropylene composite materials, reaching the level of a new material composite system, and is suitable for high-demand automotive exterior painted products.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials and processing thereof, and relates to a recycled polypropylene composite material with high surface finish and high paint adhesion and a preparation method thereof. Background Art
[0003] Among automotive plastics, polypropylene has become one of the most widely used plastic materials for automotive parts, accounting for about 40% of automotive plastics, due to its light weight, low price, easy processing, corrosion resistance, impact strength, flexural resistance and good electrical insulation. Therefore, major automobile manufacturers have sought to replace traditional polypropylene composite materials with recycled polypropylene composite materials to reduce the carbon emissions of the entire vehicle. At present, the main source of recycled polypropylene is post-consumer recycled materials, namely PCR materials, mainly recycled polypropylene materials from home appliances, recycled daily consumer goods, and recycled polypropylene materials from scrapped cars. From the perspective of recycling difficulty, scale, purity and performance of recycled materials, polypropylene recycled from home appliances, especially washing machine barrels, has good purity and excellent comprehensive performance. At present, it has been industrialized in automotive exterior system parts, such as automotive underbody guards, wheel covers, bumper brackets and other exterior non-appearance parts. As for the exterior bumper body, tailgate outer panel, fender and other painted parts with large consumption, the surface of recycled polypropylene cannot be cleaned absolutely during the disassembly and recycling process. There are pits, impurities and small molecules on the surface, which makes its surface adhesion poor and its bonding with the paint surface poor, limiting its further development and application in painted parts. Therefore, how to make the recycled polypropylene material have better paint adhesion while maintaining the original mechanical properties has become an urgent problem to be solved in the development of this type of material.
[0004] At present, there have been some studies on the paint adhesion of recycled polypropylene materials in the industry. Chinese patent CN117106260 discloses a polypropylene material and its preparation method and application, which improves the adhesion of recycled polypropylene paint by adding polyurethane as a toughening agent, kaolin and graphene oxide as reinforcing agents, and supplemented with compatibilizers and coupling agents. However, adding too much polyurethane will affect the shrinkage rate and linear expansion coefficient of the composite system, which is not mentioned in this patent; Chinese patent CN113999575 discloses a recycled polypropylene spray material and its preparation method, which improves the adhesion of recycled polypropylene material and paint by adding a high melting point toughening agent and a silica-grafted butyl acrylate adhesive. On the one hand, the preparation process of the silica-grafted butyl acrylate adhesive is complicated and the industrialization cost is high. On the other hand, the resulting composite material has poor rigidity-toughness balance performance and cannot be used for exterior spray paint bumpers and other parts with high rigidity-toughness balance requirements. Summary of the invention
[0005] The purpose of the present invention is to provide a recycled polypropylene composite material with high surface finish and high paint adhesion and a preparation method thereof, so as to solve the above problems of the prior art.
[0006] In order to improve the surface adhesion of recycled polypropylene composite materials and paints, and at the same time improve the surface finish of composite products, the present invention adopts a high-performance composite masterbatch to replace the traditional method of directly using talcum powder + additives, making full use of the mold expansion effect of the polymer. In the process of twin-screw extrusion or injection molding, polypropylene with an ultra-high melt flow rate flows to the outside of the melt, driving the modified chlorinated polypropylene and epoxy resin to be evenly dispersed and enriched in the surface layer of the material, thereby greatly improving the surface polarity of the recycled polypropylene composite system; at the same time, the interlayer gap characteristics of the regular layered structure of the high-diameter-to-thickness ratio talcum powder in the high-performance composite masterbatch can further adsorb paint components with smaller volume molecules, thereby further improving the adhesion of the recycled polypropylene substrate and the paint, and the paint adhesion of the obtained recycled polypropylene composite material can reach the level of the new material composite system. At the same time, it is also found that after the introduction of the high-performance composite masterbatch, the surface finish of the product obtained by the recycled polypropylene composite system of the present invention is significantly improved, and there are no appearance defects such as pitting and shrinkage pits on the surface, which is suitable for the field of spray-painted products with high appearance requirements such as automotive exterior bumpers and tailgate outer panels.
[0007] To achieve the above object, the present invention specifically adopts the following technical solutions:
[0008] A recycled polypropylene composite material with high surface finish and high paint adhesion, comprising the following raw materials in percentage by weight:
[0009]
[0010]
[0011] In the polypropylene composite material system to which the present invention is applicable,
[0012] The recycled polypropylene resin is a recycled polypropylene resin obtained by recycling polypropylene from household appliance housings, consumer products, etc., and has a melt flow rate of 10 to 50 g / 10 min at 230° C. and 2.16 kg load. As an embodiment, the recycled polypropylene resin is obtained by recycling and granulating the inner drum of a washing machine, and has a melt flow rate of 25 to 35 g / 10 min at 230° C. and 2.16 kg load.
[0013] The high-performance composite masterbatch is prepared from the following components by weight: 10 parts of ultra-high fluidity polypropylene, 15 parts of modified chlorinated polypropylene, 70 parts of talcum powder, 2 parts of epoxy resin, 2 parts of compatibilizer, and 1 part of lubricant.
[0014] In the high-performance composite masterbatch, the ultra-high fluidity polypropylene is metallocene-catalyzed polypropylene, and under the conditions of 230° C. and 2.16 kg load, the melt flow rate is 100-200 g / 10 min.
[0015] In the high-performance composite masterbatch, the ultra-high fluidity polypropylene has a melt flow rate of 150 g / 10 min at 230° C. and 2.16 kg load.
[0016] In the high-performance composite masterbatch, the modified chlorinated polypropylene is organosiloxane modified chlorinated polypropylene, the grafting rate of organosiloxane functional groups is 1.5-2.5%, and the chlorination degree of the modified chlorinated polypropylene is 10-20%. As an embodiment, the organosiloxane modified chlorinated polypropylene has an organosiloxane functional group grafting rate of 2.5%, and the chlorination degree of the modified chlorinated polypropylene is 15%;
[0017] In the high-performance composite masterbatch, the talcum powder is a talcum powder with a high aspect ratio, the aspect ratio is 10 to 30, the mesh number is 5000 to 10000 mesh, and it has the characteristics of a regular layered structure; as an embodiment, the talcum powder has a mesh number of 10000 mesh and an aspect ratio of 25.
[0018] In the high-performance composite masterbatch, the compatibilizer is maleic anhydride grafted polypropylene with a density of 0.89-0.91 g / cm 3 The grafting rate is 0.5-2.0%, and it is obtained by melt extrusion modification of any block copolymerized polypropylene by maleic anhydride. As an embodiment, the maleic anhydride grafted polypropylene has a density of 0.90 g / cm 3 , the grafting rate is 1.5%;
[0019] In the high-performance composite masterbatch, the lubricant is compounded with ethylene bisstearamide and stearate in a ratio of 1:1, wherein the ethylene bisstearamide is N,N_ethylene bisstearamide, and the stearate is magnesium stearate.
[0020] In the polypropylene composite material system, the elastomer is an ethylene-octene linear copolymer or an ethylene-butene linear copolymer or a combination of the two, and the density is 0.88-0.90 g / cm 3 , the melt flow rate is 0.5-10 g / 10 min. As an embodiment, the elastomer is an ethylene-octene linear copolymer with a density of 0.88 g / cm 3 , the melt flow rate is 2g / 10min.
[0021] In the polypropylene composite material system, the antioxidant is an antioxidant considered necessary by those skilled in the art, mainly one or a mixture of two or more of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester (antioxidant 1010), tris[2,4-di-tert-butylphenyl] phosphite (antioxidant 168), octadecyl thiodipropionate (antioxidant DSTP), and β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate n-octadecyl alcohol ester (antioxidant 1076). As an embodiment, the antioxidant is a mixture of antioxidant 1010, antioxidant DSTP and antioxidant 168, and the mixing ratio is 1:1:2.
[0022] In the polypropylene composite material system, the other additives are mainly one or a combination of various color components, light stabilizers, processing aids, etc. that are considered necessary by those skilled in the art.
[0023] The preparation method of the above-mentioned recycled polypropylene composite material with high surface finish and high paint adhesion comprises the following specific steps:
[0024] A. Preparation of high performance composite masterbatch:
[0025] According to the weight components, ultra-high flow polypropylene, modified chlorinated polypropylene, talcum powder, epoxy resin, compatibilizer and lubricant are added to the high-speed mixer for uniform mixing, and then transferred to the mixing chamber of the internal mixer for high-speed internal mixing. Then, the mixed block material is transferred to the double-wrist feeding port for feeding, and extruded, air-cooled and granulated by a single screw extruder to prepare high-performance composite masterbatch. The temperature of the internal mixing chamber in the internal mixer is set at 170-190℃, the diameter of the single screw is 70mm, the aspect ratio is 12, and the single screw extruder is divided into three sections for temperature control. The temperatures of each section from the feeding port to the die are 180℃, 190℃ and 200℃ respectively.
[0026] B. Preparation of recycled polypropylene composite materials with high surface finish and high paint adhesion:
[0027] (1) Weigh and prepare the above components according to the mass ratio;
[0028] (2) placing recycled polypropylene resin, high-performance composite masterbatch, elastomer, antioxidant, and other additives in a high-speed mixer and mixing at high speed for 5 to 10 minutes;
[0029] (3) The mixed raw materials are placed in a twin-screw extruder, melt extruded, and granulated. The process is: zone 1 180-190°C, zone 2 190-200°C, zone 3 200-210°C, zone 4 200-210°C; the residence time of the entire extrusion process is 1-2 minutes, the pressure is 12-18 MPa, and the exhaust vacuum reaches 5-20 kPa. The extruder head is equipped with a 80 / 100 mesh double-layer filter, and the screen replacement frequency is 2-4 hours / time.
[0030] The advantages of the present invention are:
[0031] (1) The present invention adopts a high-performance composite masterbatch to replace the traditional method of directly using talcum powder + additives in the formula design of the recycled polypropylene composite material. The high-performance composite masterbatch uses ultra-high fluidity polypropylene as a carrier and fully utilizes the die expansion effect of the polymer. During the twin-screw extrusion or injection molding process, the polypropylene with ultra-high fluidity flows to the outside of the melt, driving the modified chlorinated polypropylene and epoxy resin to be evenly dispersed and enriched on the surface of the material, thereby greatly improving the surface polarity of the recycled polypropylene composite system;
[0032] (2) The present invention can achieve higher paint adhesion in the regenerated composite system by adding less modified chlorinated polypropylene and epoxy resin as a whole.
[0033] (3) The present invention utilizes the interlayer gap characteristics of the regular layered structure of high-diameter-to-thickness ratio talc powder in the high-performance composite masterbatch to further adsorb paint components with smaller volume molecules during the painting process, thereby further improving the adhesion between the recycled polypropylene substrate and the paint. The paint adhesion of the resulting recycled polypropylene composite material can reach the level of a new material composite system.
[0034] (4) The addition of maleic anhydride grafted polypropylene in the high-performance composite masterbatch of the present invention can increase the interfacial bonding force and compatibility between talc and polypropylene, thereby further improving the comprehensive mechanical properties of the recycled polypropylene composite material system;
[0035] (5) The present invention also found that after the introduction of high-performance composite masterbatch, the surface finish of the product obtained from the recycled polypropylene composite system is significantly improved, and there are no appearance defects such as pitting and shrinkage pits on the surface. After painting, the surface of the product is smooth and has no appearance defects.
[0036] (6) The recycled polypropylene composite material with high surface finish and high paint adhesion proposed by the present invention has a simple preparation process and low production cost. DETAILED DESCRIPTION
[0037] The present invention is further described in detail below by way of examples and comparative examples, but the present invention is not limited to the scope of the examples.
[0038] Example 1
[0039] The main components of the polypropylene composite material of the present invention include 70.5% recycled polypropylene, 15% high-performance composite masterbatch A, 12% elastomer, 0.5% antioxidant and 2% other additives. The main components of the high-performance composite masterbatch A are 10% ultra-high fluidity polypropylene, 15% modified chlorinated polypropylene, 70% talcum powder, 2% epoxy resin, 2% compatibilizer and 1% lubricant.
[0040] Example 2
[0041] The main components of the polypropylene composite material of the present invention include 61.5% recycled polypropylene, 22% high-performance composite masterbatch A, 14% elastomer, 0.5% antioxidant and 2% other additives. The main components of the high-performance composite masterbatch A are the same as those in Example 1.
[0042] Example 3
[0043] The main components of the polypropylene composite material of the present invention include 63.5% recycled polypropylene, 22% high-performance composite masterbatch A, 12% elastomer, 0.5% antioxidant and 2% other additives. The main components of the high-performance composite masterbatch A are the same as those in Example 1.
[0044] Example 4
[0045] The main components of the polypropylene composite material of the present invention include 54.5% recycled polypropylene, 29% high-performance composite masterbatch A, 14% elastomer, 0.5% antioxidant and 2% other additives. The main components of the high-performance composite masterbatch A are the same as those in Example 1.
[0046] Example 5
[0047] The main components of the polypropylene composite material of the present invention include 52.5% recycled polypropylene, 29% high-performance composite masterbatch A, 16% elastomer, 0.5% antioxidant and 2% other additives. The main components of the high-performance composite masterbatch A are the same as those in Example 1.
[0048] Example 6
[0049] The main components of the polypropylene composite material of the present invention include 50.5% recycled polypropylene, 29% high-performance composite masterbatch A, 18% elastomer, 0.5% antioxidant and 2% other additives. The main components of the high-performance composite masterbatch A are the same as those in Example 1.
[0050] Comparative Example 1
[0051] The main components of the polypropylene composite material of the present invention include 52.5% recycled polypropylene, 29% high-performance composite masterbatch B, 16% elastomer, 0.5% antioxidant and 2% other additives. The main components of the high-performance composite masterbatch B are 25% ultra-high fluidity polypropylene, 70% talcum powder, 2% epoxy resin, 2% compatibilizer and 1% lubricant.
[0052] Comparative Example 2
[0053] The main components of the polypropylene composite material of the present invention include 52.5% recycled polypropylene, 29% high-performance composite masterbatch C, 16% elastomer, 0.5% antioxidant and 2% other additives. The main components of the high-performance composite masterbatch C are 12% ultra-high fluidity polypropylene, 15% modified chlorinated polypropylene, 70% talcum powder, 2% compatibilizer and 1% lubricant.
[0054] Comparative Example 3
[0055] The main components of the polypropylene composite material of the present invention include 52.5% recycled polypropylene, 29% high-performance composite masterbatch D, 16% elastomer, 0.5% antioxidant and 2% other additives. The main components of the high-performance composite masterbatch D are 12% ultra-high fluidity polypropylene, 15% modified chlorinated polypropylene, 70% talcum powder, 2% epoxy resin and 1% lubricant.
[0056] Comparative Example 4
[0057] The main components of the polypropylene composite material of the present invention include 52.5% recycled polypropylene, 29% high-performance composite masterbatch E, 16% elastomer, 0.5% antioxidant and 2% other additives. The main components of the high-performance composite masterbatch E are 10% new polypropylene resin, 15% modified chlorinated polypropylene, 70% talcum powder, 2% epoxy resin, 2% compatibilizer and 1% lubricant.
[0058] Comparative Example 5
[0059] The polypropylene composite material of the invention mainly comprises 67.44% of new polypropylene resin, 15.4% of talc, 14% of elastomer, 0.44% of compatibilizer, 0.22% of lubricant, 0.5% of antioxidant and 2% of other additives.
[0060] Comparative Example 6
[0061] The polypropylene composite material of the invention mainly comprises 60.33% of new polypropylene resin, 20.3% of talc, 16% of elastomer, 0.58% of compatibilizer, 0.29% of lubricant, 0.5% of antioxidant and 2% of other additives.
[0062] Comparative Example 7
[0063] The polypropylene composite material of the invention mainly comprises 52.5% recycled polypropylene resin, 2.9% ultra-high fluidity polypropylene, 4.35% modified chlorinated polypropylene, 20.3% talcum powder, 16% elastomer, 0.58% epoxy resin, 0.58% compatibilizer, 0.29% lubricant, 0.5% antioxidant and 2% other additives.
[0064] The contents of the components in the examples and comparative examples of the present invention are shown in Table 1.
[0065] Table 1 Main component contents (mass percentage) in the embodiments and comparative examples
[0066]
[0067]
[0068] The raw materials described in the embodiments and comparative examples in Table 1 above are as follows:
[0069] The recycled polypropylene resin was produced by GreenMe Co., Ltd., with a brand name of A310 and a melt flow rate of 35 g / 10 min;
[0070] The new polypropylene resin is made of EP5075X and BX3500 in a ratio of 2:1. The EP5075X is produced by China SABIC and has a melt flow rate of 60g / 10min. The BX3500 is produced by SK Company of South Korea and has a melt flow rate of 8g / 10min.
[0071] The ultra-high fluidity polypropylene is MH7900 produced by LG, with a melt flow rate of 150 g / 10 min;
[0072] The modified chlorinated polypropylene is organic siloxane modified chlorinated polypropylene, the organic siloxane functional group grafting rate is 2.5%, the chlorination degree of the modified chlorinated polypropylene is 15%, and it is homemade;
[0073] The talcum powder is about 10000 mesh talcum powder with a diameter-to-thickness ratio of 25, and comes from Shanghai Yuanjiang Chemical Co., Ltd.
[0074] The elastomer is a thermoplastic POE elastomer produced by LG, with a brand number of 168.
[0075] The epoxy resin was KD-213 produced by Guodu Chemical;
[0076] The compatibilizer is maleic anhydride grafted polypropylene with a grafting rate of 1.5%, produced by Prilon.
[0077] The lubricant is compounded with ethylene bis stearyl amide and stearate in a ratio of 1:1, wherein the ethylene bis stearyl amide is N,N_ethylene bis stearamide, Sigma-Aldrich (Shanghai) Trading Co., Ltd., and the stearate is magnesium stearate, from Shanghai Yuanye Biotechnology Co., Ltd.;
[0078] The antioxidant is a compound antioxidant of 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) / DSTP (octadecyl thiodipropionate) / antioxidant 168 (tris[2,4-di-tert-butylphenyl]phosphite) in a mass ratio of 1:1:2, all of which are commercially available.
[0079] Other additives mainly refer to color components, light stabilizers, etc.
[0080] The specific implementation methods of the above embodiments and comparative examples 1-4 are as follows:
[0081] A. Preparation of high performance composite masterbatch:
[0082] According to the mass ratio, the components of the high-performance composite masterbatch in the embodiment and comparative examples 1-4 are added to the high-speed mixer for uniform mixing, and then transferred to the mixing chamber of the internal mixer for high-speed internal mixing and mixing, and then the mixed block material is transferred to the double-wrist feeding port for feeding, and extruded, air-cooled and granulated by a single screw extruder to prepare a high-performance composite masterbatch. The temperature of the internal mixing chamber in the internal mixer is set at 170-190°C, the diameter of the single screw is 70mm, and the aspect ratio is 12; the single screw extruder is divided into three sections for temperature control, and the temperatures of each section from the feeding port to the die are 180°C, 190°C, and 200°C, respectively.
[0083] B. Preparation of recycled polypropylene composite materials with high surface finish and high paint adhesion:
[0084] (1) The components in Examples and Comparative Examples 1-4 were weighed and mixed according to the mass ratio;
[0085] (2) Place the weighed components in a high-speed mixer and mix at high speed for 5 to 10 minutes;
[0086] (3) The mixed raw materials are placed in a twin-screw extruder, melt extruded, and granulated. The process is: zone 1 180-190°C, zone 2 190-200°C, zone 3 200-210°C, zone 4 200-210°C; the residence time of the entire extrusion process is 1-2 minutes, the pressure is 12-18 MPa, and the exhaust vacuum reaches 5-20 kPa. The extruder head is equipped with a 80 / 100 mesh double-layer filter, and the screen replacement frequency is 2-4 hours / time.
[0087] The specific implementation methods of the above comparative examples 5-7 are as follows:
[0088] (1) Weigh and prepare the components in Comparative Examples 5-7 according to the mass ratio;
[0089] (2) Place the weighed components in a high-speed mixer and mix at high speed for 5 to 10 minutes;
[0090] (3) The mixed raw materials are placed in a twin-screw extruder, melt extruded, and granulated. The process is: zone 1 180-190°C, zone 2 190-200°C, zone 3 200-210°C, zone 4 200-210°C; the residence time of the entire extrusion process is 1-2 minutes, the pressure is 12-18 MPa, and the exhaust vacuum reaches 5-20 kPa. The extruder head is equipped with a 80 / 100 mesh double-layer filter, and the screen replacement frequency is 2-4 hours / time.
[0091] The composite material particles prepared according to the above examples and comparative examples were dried in a blast oven at 80-100° C. for 2 hours, and then the dried particles were injection molded on an injection molding machine, and then the performance was tested.
[0092] Basic mechanical properties test: Density is tested according to ISO1183-1 standard; Melt index is tested according to ISO1133-1 standard, the test temperature is 230℃, and the load is 2.16kg; Flexural modulus is tested according to ISO178 standard, the sample size is 80*10*4mm, the span is 64mm, and the bending speed is 2mm / min; Notched impact strength is tested according to ISO179-1 standard, the sample size is 80*10*4mm, and the notch depth is one fifth of the sample width;
[0093] Surface tension test: Use surface dyne value for test characterization, injection mold 150*100*3.2mm sample, use dyne pen to test the surface dyne value of the sample before and after flame treatment. The larger the dyne value, the greater the surface tension of the sample.
[0094] High-pressure flushing performance test: injection molding 150*100*3.2mm sample, flame and spraying treatment using mass-produced paint and process, high-pressure flushing test after aging at room temperature for 7 days; the specific experimental method is: use a knife to draw × lines to the bottom layer of the coating on the sample after spraying, the length of each line is 100mm, aim the high-pressure nozzle at each edge of the × line for spraying, the distance between the nozzle and the line is 13cm, the spray angle is 90°, the water temperature is 60℃, the flow rate is 11.5L / min, and the spray time is 60s. According to the degree of coating shedding after spraying, it is graded as 1 (no coating shedding), 2 (slight coating shedding at × line), 3 (obvious coating shedding at × line), 4 (large area coating shedding), the smaller the level, the better the adhesion between the substrate and the paint.
[0095] Surface finish assessment: Injection molded 150*100*3.2mm samples, count the appearance defects such as shrinkage pits, pitting, impurities on the sample surface under standard light source, no appearance defects is level 0, the average number of appearance defects per sample surface is 1-2 is level 1, the average number of appearance defects per sample surface is between 3-5 is level 2, and the average number of appearance defects per sample surface is more than 5 is level 3.
[0096] The performance test results of the recycled polypropylene composite materials of Examples 1 to 6 of the present invention and Comparative Examples 1 to 7 are shown in Table 2, respectively.
[0097] Table 2 Material performance test data in the embodiments and comparative examples
[0098]
[0099]
[0100] From the data results of the embodiments and comparative examples 5-6 in the above table, it can be found that after the introduction of the high-performance composite masterbatch with ultra-high fluidity polypropylene as the carrier, the surface tension and high-pressure water flushing performance of the recycled polypropylene composite system before and after flame treatment reach or even exceed the level of the new material system, the surface dyne value of the sample after flame treatment can reach 50+, and there is no coating shedding on the surface of the paint sample after high-pressure water flushing. It can be seen from the data results of Example 5 and Comparative Examples 1-2 that the single addition of modified chlorinated polypropylene and epoxy resin in the high-performance composite masterbatch cannot achieve a high surface paint adhesion; it can be seen from the data results of Example 5 and Comparative Example 3 that the addition of maleic anhydride grafted polypropylene as a compatibilizer in the high-performance composite masterbatch can increase the interfacial bonding force and compatibility between talc and polypropylene, thereby improving the comprehensive mechanical properties of the recycled polypropylene composite material system; it can be seen from the data results of Example 5 and Comparative Examples 4 and 7 that the ultra-high fluidity polypropylene carrier in the high-performance composite masterbatch plays a vital role in the system, especially pre-processing into a high-performance composite masterbatch, which can maximize the demoulding expansion effect of the polymer, and when a relatively small amount of modified chlorinated polypropylene and epoxy resin are added as a whole, the recycled composite system can achieve a higher level of paint adhesion. At the same time, from the comparison between Examples 1-6 and Comparative Examples 1-2 and Comparative Examples 5-6, it was unexpectedly found that after the introduction of the high-performance composite masterbatch, the surface finish of the recycled composite material system was level 0, and there were no appearance defects such as shrinkage pits, pitting, impurities, etc. on the surface of the sample, which could reach the same level as the new polypropylene composite material, and was suitable for molding and processing of painted parts with high requirements on appearance.
Claims
1. A recycled polypropylene composite material with high surface finish and high paint adhesion, characterized in that: The raw materials are prepared according to the following weight percentages:
2. A recycled polypropylene composite material with high surface finish and high paint adhesion according to claim 1, characterized in that: The recycled polypropylene resin is a recycled polypropylene resin prepared by recycling polypropylene from household appliance shells, consumer products, etc.
3. The recycled polypropylene composite material with high surface finish and high paint adhesion according to claim 1, characterized in that: The regenerated polypropylene resin has a melt flow rate of 10 to 50 g / 10 min under the conditions of 230° C. and 2.16 kg load.
4. The recycled polypropylene composite material with high surface finish and high paint adhesion according to claim 1, characterized in that: The high-performance composite masterbatch is prepared from the following components by weight percentage: Ultra-high flow polypropylene 10%; Modified chlorinated polypropylene 15%; Talc 70%; Epoxy resin 2%; Compatibilizer 2%; Lubricant 1%.
5. The high-performance composite masterbatch according to claim 4, characterized in that: The ultra-high fluidity polypropylene is metallocene-catalyzed polypropylene, and under the conditions of 230° C. and 2.16 kg load, the melt flow rate is 100-200 g / 10 min.
6. The high-performance composite masterbatch according to claim 4, characterized in that: The modified chlorinated polypropylene is organic siloxane modified chlorinated polypropylene, the organic siloxane functional group grafting rate is 1.5-2.5%, and the chlorination degree of the modified chlorinated polypropylene is 10-20%.
7. The high-performance composite masterbatch according to claim 4, characterized in that: The talcum powder has a high diameter-to-thickness ratio of 10-30, a mesh number of 5000-10000 meshes, and has the characteristics of a regular layered structure.
8. The high-performance composite masterbatch according to claim 4, characterized in that: The compatibilizer is maleic anhydride grafted polypropylene, with a density of 0.89-0.91 g / cm3 and a grafting rate of 0.5-2.0%, and is obtained by melting and extruding any block copolymerized polypropylene modified by maleic anhydride.
9. The high-performance composite masterbatch according to claim 4, characterized in that: The lubricant is compounded with ethylene bis stearyl amide and stearate in a ratio of 1:1, wherein the ethylene bis stearyl amide is N,N_ethylene bis stearate amide, and the stearate is magnesium stearate.
10. The recycled polypropylene composite material with high surface finish and high paint adhesion according to claim 1, characterized in that: The elastomer is an ethylene-octene linear copolymer or an ethylene-butene linear copolymer or a combination of the two, and has a density of 0.88-0.90 g / cm 3 , the melt flow rate is 0.5~10g / 10min.
11. The recycled polypropylene composite material with high surface finish and high paint adhesion according to claim 1, characterized in that: The antioxidant is an antioxidant considered necessary by those skilled in the art, and is mainly one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1010), tris[2,4-di-tert-butylphenyl]phosphite (antioxidant 168), octadecyl thiodipropionate (antioxidant DSTP), and n-octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1076), or a mixture of two or more thereof.
12. The recycled polypropylene composite material with high surface finish and high paint adhesion according to claim 1, characterized in that: The other additives are mainly one or a combination of various color components, light stabilizers, and processing aids that are considered necessary by those skilled in the art.
13. The recycled polypropylene composite material with high surface finish and high paint adhesion according to any one of claims 1 to 12, characterized in that: The specific steps are as follows: A. Preparation of high performance composite masterbatch: Ultra-high fluidity polypropylene, modified chlorinated polypropylene, talcum powder, epoxy resin, compatibilizer and lubricant are added to a high-speed mixer according to weight percentage and mixed evenly, and then transferred to the mixing chamber of the internal mixer for high-speed internal mixing and mixing, and then the mixed block material is transferred to the double-wrist feeding port for feeding, and extruded, air-cooled and granulated by a single screw extruder to prepare a high-performance composite masterbatch; wherein the temperature of the internal mixing chamber in the internal mixer is set at 170-190°C, the diameter of the single screw is 70mm, the aspect ratio is 12, and the single screw extruder is divided into three sections for temperature control, and the temperatures of each section from the feeding port to the die are 180°C, 190°C and 200°C respectively; B. Preparation of recycled polypropylene composite materials with high surface finish and high paint adhesion: (1) Weigh and prepare the above components according to the mass ratio; (2) placing recycled polypropylene resin, high-performance composite masterbatch, elastomer, antioxidant, and other additives in a high-speed mixer and mixing at high speed for 5 to 10 minutes; (3) placing the mixed raw materials in a twin-screw extruder, and subjecting them to melt extrusion and granulation, the process is as follows: zone 1 180-190° C., zone 2 190-200° C., zone 3 200-210° C., zone 4 200-210° C.; The residence time of the entire extrusion process is 1 to 2 minutes, the pressure is 12 to 18 MPa, and the exhaust vacuum reaches 5 to 20 kPa. The extruder head is equipped with a 80 / 100 mesh double-layer filter, and the frequency of screen replacement is 2 to 4 hours / time.
Citation Information
Patent Citations
Method for improving strength of waste polypropylene melt
CN106496771A
Low-odor, high-performance and environment-friendly polypropylene composite material and preparation method thereof
CN112625347A
High-performance thin-wall polypropylene composite material capable of improving mold sticking and preparation method of high-performance thin-wall polypropylene composite material
CN114369314A
Environment-friendly regenerated polypropylene modified material special for automobile exterior trimming and preparation method
CN114806004A
Polypropylene material as well as preparation method and application thereof
CN117106260A